Niger : 2008 Article IV Consultation and First Review Under the Three-Year Arrangement Under the Poverty Reduction and Growth Facility, and Request for Waivers and Modification of Performance Criteria; Staff Report; Staff Supplement; Public Information Notice and Press Release on the Executive Board Discussion; and Statement by the Executive Director for Niger. (IMF Staff Country Reports; Country Report ;, 2009)
The staff report for Niger's 2008 Article IV Consultation, first review under the Three-Year Arrangement Under the Poverty Reduction and Growth Facility, and request for Waivers and Modification of Performance Criteria is discussed. The authorities initially suspended taxes on critical foodstuffs but also relied on targeted interventions for vulnerable groups, which made it possible to end the tax suspensions in September. They also froze the retail price of petroleum products, in effect suspending part of the tax on fuel.